Motivasi Mahasiswa Pendidikan Sosiologi Dalam Mengikuti Organisasi Himpunan Mahasiswa Pendidikan Sosiologi (HMPS) FKIP ULM - Ulfah, Ulfah; Azkia, Laila; Nur, Rahmat (Universitas Lambung Mangkurat, 2024)
Motivation influences individual behavior, with motivation individuals can exert their best abilities for HMPS. So that it can produce something, both for the individual and for HMPS. This research aims to (1) find the driving factors for Sociology Education students in joining the Sociology Education Student Association (HMPS). (2) find the goals that members want to achieve in participating in HMPS. (3) finding the efforts of HMPS members in achieving goals. This study used qualitative research methods. The data sources used were purposive sampling and snowball sampling. There were 10 informants in this study. With the specified informant criteria, namely the Sharing Committee (SC) and department heads. Data collection was carried out using observation, interviews and documentation techniques. The data analysis technique used is by reducing data, presenting data, and drawing conclusions. Data validity testing techniques, namely by extending observations, increasing persistence, and triangulation. The results of this research show that (1) the driving factors for Sociology Education students in taking HMPS, namely a) because of the desire to improve their own abilities, b) because they are interested in the HMPS work program, c) because of the environment around the students. (2) goals to be achieved, namely a) goals to be achieved for oneself, b) goals to be achieved for HMPS. (3) HMPS members' efforts to achieve goals, namely a) members' efforts to achieve goals for themselves, b) members' efforts to achieve goals for HMPS.